2007
DOI: 10.1111/j.1574-6941.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of 16S rRNA gene-targetted fluorescence in situ hybridization and restriction fragment length polymorphism to study porcine microbiota along the gastrointestinal tract in response to different sources of dietary fibre

Abstract: A total of 32 pigs of 15+/-0.38 kg body weight were fed for 6 weeks one of four diets differing in their source of dietary fibre. FISH was used to quantify the main bacterial groups in the pig gut using the following probes: Eub338, Bac303, Rfla729, Rbro730, Erec482, Fprau645, Prop853, Str493 and Lab158. FISH counts revealed important differences at four sites along the pig gastrointestinal tract, but we were unable to show differences related to diets. Stomach and jejunal samples gave total bacterial counts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 38 publications
(36 reference statements)
3
33
2
1
Order By: Relevance
“…The predominant phyla present in the feces of both feeding groups of pigs at all time points were the Firmicutes and Bacteroidetes, similar to previous studies with both pig and human subjects (7,13,23), suggesting that the pig is a good animal model for studying the GI microbiome and the consequences of microbiota manipulation. The microbial populations were not statistically different between individuals at the start of the trial (day 1, no milk) at the phylum level, indicating that all pigs were starting with similar fecal microbiotas.…”
Section: Discussionsupporting
confidence: 85%
“…The predominant phyla present in the feces of both feeding groups of pigs at all time points were the Firmicutes and Bacteroidetes, similar to previous studies with both pig and human subjects (7,13,23), suggesting that the pig is a good animal model for studying the GI microbiome and the consequences of microbiota manipulation. The microbial populations were not statistically different between individuals at the start of the trial (day 1, no milk) at the phylum level, indicating that all pigs were starting with similar fecal microbiotas.…”
Section: Discussionsupporting
confidence: 85%
“…However, to maintain normal gut function, a minimum level of fibre has to be included in the diet (Wenk, 2001) and inclusion of dietary fibre can be a strategy to change the structure of the gut microbial communities (Castillo et al, 2007). The microbial ecosystem in the gastrointestinal (GI) tract is characterized by a high population density, wide diversity and complexity of hostmicrobe and microbe-microbe interactions (Zoetendal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial ecosystem in the gastrointestinal (GI) tract is characterized by a high population density, wide diversity and complexity of hostmicrobe and microbe-microbe interactions (Zoetendal et al, 2004). However, the knowledge about the gut microbial diversity is still far from complete and the use of molecular techniques has revealed that many of the pig gut microbial communities have not previously been cultured (Leser et al, 2002;Castillo et al, 2007;Patterson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The porcine intestinal microbiota change in response to dietary carbohydrate composition due to specific substrate preferences of bacteria (6). Therefore, inclusion of specific nonstarch polysaccharides (NSP) in the diet of pigs allows manipulation of the composition of the intestinal microbiota.…”
mentioning
confidence: 99%